Presbiphonya - Bruzzi, Caterina; Salsi, Daria; Minghetti, Domenico; Negri, Maurizio; Casolino, Delfo; Sessa, Michele (Acta Biomedica Atenei Parmensis, 2017)
Aim: This article attempts to describe the aging process of the vocal folds and the main features of the aged voice. Background: In the world ageing population era, aging diseases and aging disorders are crucial. Voice disorders (presbyphonia) are common in the elderly and have a significant impact on communication and quality of life. Some of these disorders depend on the vocal folds, which consist of an extracellular matrix (ECM), fibrous proteins, interstitial proteins, and glycosaminoglycans. The density and spatial arrangement of these elements are important, as changes in their deposition can alter the biomechanical properties and vibratory function of the vocal folds. Discussion: The aging voice process is analyzed in detail from mechanical factors like pulmonary bellows alteration, to hormonal factors and life style. Conclusions: The elderly people undergoe mechanical, anatomical and functional changes: alterations of the pulmonary bellows, systemic changes like hormonal disregulation, and laryngeal changes, that resulting in hoarseness, which is difficult to treat.